IMPLEMENTATION OF INCLUSIVE EDUCATION AT THE PILOT INCLUSION SCHOOL IN PONTIANAK - Marmawi Marmawi; Muhammad Ali; Andini Linarsih; Dian Miranda (Universitas Tanjungpura, 2022)
This study aims to provide an overview of the implementation of inclusive education at the Inclusive Pilot School in Pontianak, particularly at the preschool level. The Pilot Inclusion Preschool in Pontianak consists of West Pontianak Integrated Kindergarten/ Preschool and North Pontianak Selayar Kindergarten. The two kindergartens provide inclusive education for children with special needs ages 4-6. The method used in this study is a descriptive method to describe inclusive education objectively in the two preschools. The techniques used in this research are observation, interviews, and documentary studies. The data needed is related to the two preschool institutions’ planning, implementation, and evaluation of inclusive education. Overall, findings revealed that the institutions have carried out planning, implementation, and evaluation in providing services to children with special needs. However, they did not entirely follow the techniqal instructions for implementing inclusive education. Keywords: Inclusive Education, Inclusive school, Preschool, Children with Special NeedsAbstrakPenelitian ini bertujuan untuk memberikan gambaran tentang pelaksanaan pendidikan inklusi di Sekolah Percontohan Inklusi di Pontianak, khususnya pada tingkat prasekolah. PAUD Inklusi Percontohan di Pontianak terdiri dari TK/PAUD Terpadu Pontianak Barat dan TK Selayar Pontianak Utara. Kedua TK tersebut menyediakan pendidikan inklusif bagi anak berkebutuhan khusus usia 4-6 tahun. Metode yang digunakan dalam penelitian ini adalah metode deskriptif untuk menggambarkan pendidikan inklusi secara objektif di kedua PAUD tersebut. Teknik yang digunakan dalam penelitian ini adalah observasi, wawancara, dan studi dokumenter. Data yang dibutuhkan terkait dengan perencanaan, pelaksanaan, dan evaluasi pendidikan inklusif kedua lembaga prasekolah tersebut. Secara keseluruhan, temuan mengungkapkan bahwa lembaga telah melakukan perencanaan, pelaksanaan, dan evaluasi dalam memberikan pelayanan kepada anak berkebutuhan khusus. Namun, mereka tidak sepenuhnya mengikuti petunjuk teknis penyelenggaraan pendidikan inklusif.Kata Kunci: Pendidikan Inklusi, Sekolah Inklusi, Prasekolah, Anak Berkebutuhan Khusus